Immunomodulation using bacterialeEnterotoxins - Simmons, Cameron (2018)
Immunologic unresponsiveness (tolerance) is a key feature of the mucosal immune system, and deliberate vaccination by a mucosal route can effectively induce immune suppression. However, some bacterial-derived proteins, e.g. cholera toxin and the heat labile toxin of Escherichia coli, are immunogenic and immunomodulatory at mucosal surfaces and can effectively adjuvant immune responses to codelivered bystander antigens. This review summarizes some of the structural and biological characteristics of these toxins and provides examples of how these properties have been exploited for tolerance induction and mucosal vaccine development.